Apprentice builders, 1946 (London, 1946)
1946 1945-1951 "Apprentice builders, 1946" [BW0135], 1946, Trades Union Congress After the Second World War, the depletion of the labour force and the urgent need for reconstruction resulted in this scheme to encourage more young men to take up apprenticeships. This guide to the Apprentice Master Scheme was produced by the Building Apprenticeship and Training Council.